Exploratory Study of the Relationship Between Happiness and the Rise of Media Consumption During COVID-19 Confinement - Muñiz-Velázquez, José Antonio; Gómez-Baya, Diego; Lozano Delmar, Javier (Frontiers in Psychology, 2021)
The confinement of the population into their homes as a result of COVID-19 has entailed a notable increase in the consumption of diverse media. This exploratory study aimed to examine how the increase in media consumption was related to subjective happiness and psychological well-being. For this purpose, a questionnaire was administered to a sample of Spanish adults (n =249; 53.8% women; aged between 18-75, M age = 42.06, SD = 12.37) to assess their consumption of different media before and during confinement. Moreover, participants were evaluated for hedonic, eudaimonic, social and experienced happiness by using the Pemberton Happiness Index (PHI). The results underlined the great increase in the consumption of television for entertainment and social networking sites (SNS) during confinement. Furthermore, it was found that higher consumption was negatively correlated with the level of happiness, so that, people who reported greater well-being, both subjective and psychological, spent less time watching television and using SNS. In contrast, no association was found between the level of happiness and the consumption of news (regardless of the media) and radio. Therefore, it seems that far from cultivating greater happiness, those who engaged in heavy consumption of television entertainment and SNS during confinement were less happy than those who did so more moderately and spent more time using other media or performing other activities.